Multiple Autopolyploid Arabidopsis lyrata Populations Stabilized by Long-Range Adaptive Introgression Across Eurasia - Scott, Alison D; Kolesnikova, Uliana K; Glushkevich, Anna; Steinmann, Laura; Tikhomirov, Nikita P; Pfordt, Ursula; Bohutínská, Magdalena; Burns, Robin; Seregin, Alexey P; Kolar, Filip; Schmickl, Roswitha; Novikova, Polina Yu (Molecular biology and evolution, 2025)
Abundance of established polyploid lineages varies across lineages, evolutionary time, and geography, suggesting both genetics and environment play a role in polyploid persistence. We show Arabidopsis lyrata is the most polyploid-rich species complex in the Arabidopsis genus, with multiple origins of autotetraploidy. This is revealed by genomic data from over 400 A. lyrata samples across Eurasia. We found over 30 previously undescribed autotetraploid populations in Siberia with a minimum of two separate origins, independent of those previously reported in Central Europe. The establishment of Siberian tetraploids is mediated by meiotic adaptation at the same genes as in European tetraploid A. lyrata and Arabidopsis arenosa, despite their genomic divergence and geographical separation. Haplotype analysis based on synthetic long-read assemblies supports the long-range introgression of adaptive alleles from the tetraploid interspecific pool of European A. lyrata and A. arenosa to tetraploid Siberian A. lyrata. Once adaptations to polyploidy emerge, they promote the establishment of new polyploid lineages through adaptive inter- and intraspecific introgression.
Keywords: tetraploidie; Evropa; genová introgrese; Europe; adaptation; haplotypy; Polyploidy; Haplotypes; introgression; Tetraploidy; polyploid; Genome, Plant; genom rostlinný; Genetic Introgression; Arabidopsis; Arabidopsis lyrata; polyploidie